Ways to Increase the Influence of Taxes in The Development of Financial and Economic Activities of Construction Enterprises - Abishov Muxammed Sarsenbaevich; Turdieva Gulayda Omirbayevna; Nuranov Ilham (International Journal on Economics, Finance and Sustainable Development, 2021)
In this article the construction enterprises are analyzed, the results of the financial and economic activities of construction enterprises directly depend on objective and subjective factors, influence on cement prices as a result of the different payment of land, given the main reason for determination of the cost of production of cement raw materials as a basis for calculating the tax on the use of subsoil.